Soil Colloids, Types and their Properties: A review - Beamlaku Alemayehu; Habtemariam Teshome (Open Journal of Bioinformatics and Biostatistics - Peertechz Publications, 2021)
The colloidal complex of soils is the fine and supreme functional section of the organic and inorganic soil particles where most of the chemical properties take place. The inorganic or clay colloidal complex of soils occurs as too fine particles and organic colloidal complex happen in the form of humus particles. Soil colloidal fraction is the site of important processes in soil, governing ion exchange, nutrient availability and fixation, and soil physical properties. Based on the silicate and crystalline nature of the colloid mineral colloids are classified into three. These are crystalline layer silicate clays, noncrystalline layer silicate clays, and non-silicate clays. The organic colloidal complex in soils is mainly because of the existence of hummus. Shape, surface area, plasticity, cohesion, swelling, shrinkage, dispersion, and flocculation are the most important properties of soil colloids.